Effect of cryostabilizing mixtures on quality of cooked sausages - Tunik, Olena; Shevchenko (Kishenko), Iryna (My University, 2025)
The optimal composition of a binary cryostabilizing mixture that preserves the structure and improves the quality of cooked sausages after freezing and thawing because of the synergistic interaction between protein and polysaccharide has been determined. Визначено оптимальний склад бінарної кріостабілізуючої суміші, яка зберігає структуру та покращує якість приготування ковбас після заморожування та розморожування завдяки синергетичній взаємодії між білком та полісахаридом.
Keywords: кафедра технології м’яса і м’ясних продуктів; кріостабілізуюча суміш; варена ковбаса; cryostat mixture; cooked sausage